Investigating the causal nexus between remittances and economic growth in Zimbabwean - Jonasi, Knowledge; Towo, Tendai; Chitombo, Ezekiel; Kondo, Talent; Dangaiso, Phillip; Vakai, Elizabeth (Annals of Management and Organization Research, 2025)
Purpose: This study aims to examine the nexus between remittances and economic growth in Zimbabwe. Methods: The research employed the Granger Causality test using annual time series data from 1980 to 2022. Preliminary diagnostic tests including stationarity, cointegration, and error correction modeling were conducted to ensure methodological rigor. Results: Findings reveal that remittances are not significantly influenced by GDP, as shown by a P-value of 0.5158. Conversely, remittances significantly drive Zimbabwe’s economic growth with a P-value of 0.0429. This highlights remittances as a vital income source that fuels household consumption, investment, and financial inclusion. The unidirectional causality emphasizes their role as a stable economic pillar independent of GDP fluctuations. Conclusion: The study demonstrates that remittances Granger-cause economic growth in Zimbabwe, but GDP does not Granger-cause remittances. This underlines the critical role of remittance inflows in sustaining consumption, supporting human capital investment, and strengthening financial development in the context of economic instability and high emigration. Limitation: The research faced challenges in accessing complete and reliable data, requiring innovative strategies to address missing values and restricting analysis to annual data. Contribution: The results provide context-specific evidence useful for scholars and policymakers in designing strategies to better channel remittances into productive investments. The study contributes by clarifying the causal mechanism between remittances and growth in Zimbabwe and offering insights for policy initiatives aimed at economic recovery and sustainable development.